Relationship Between the Drop Rate of Standing Blood Pressure and Major Adverse Cardiovascular Events - Wenqin Cai; Yuexian Yao; Suli Zheng; Wanting Chen; Lingxin Bao; Jinzi Su; Li Luo; Liangdi Xie (The Journal of Clinical Hypertension)
ABSTRACT Orthostatic hypotension (OH) is defined as a decrease of ≥20 mm Hg systolic blood pressure (SBP) or ≥10 mm Hg diastolic blood pressure (DBP) within 3 min after standing. OH was associated with an increased risk of major adverse cardiovascular events (MACEs) and mortality. As an indicator reflecting the characteristics of orthostatic blood pressure (BP) changes, there is currently no research available on the relationship between the orthostatic BP drop rate and MACEs or mortality. A total of 448 hospitalized patients (mean age 62.07 ± 12.15 years, 35.49% female) completed the follow‐up. The median follow‐up duration was 5.09 years (0.29–6.13 years). Ninety‐two patients (20.54%) developed OH, 12 patients died (2.68%), and 21 patients developed MACEs (4.69%), including 8 cases of non‐fatal acute myocardial infarction (MI), 3 cases of non‐fatal stroke, and 10 cases died of cardiovascular disease and stroke. Patients were categorized into the BPdrop_rate_high group (defined as SBP drop rate ≥ 15% and/or DBP drop rate ≥ 5% within 3 min after standing) and the BPdrop_rate_normal group (defined as SBP drop rate < 15% and DBP drop rate < 5% within 3 min after standing). The Chi‐square test and Kaplan‐Meier survival analysis indicated that the BPdrop_rate_high group had a higher risk of MACEs and mortality than the BPdrop_rate_normal group (all p < 0.05). The Receiver Operating Characteristic (ROC) analysis demonstrated SBP drop rate ≥ 15% and/or DBP drop rate ≥ 5% within 3 min after standing has high diagnostic accuracy for OH, with an area under the curve (AUC) of 0.918.Cox regression analysis revealed that the cumulative survival rate of the BPdrop_rate_normal group was significantly higher than that of the BPdrop_rate_high group (98.45% vs. 93.69%, HR 0.304, 95% CI 0.095–0.969, p = 0.044). This study proposes a novel diagnostic threshold (SBP drop ≥15% and/or DBP drop ≥5% within 3 min after standing) for OH as a strong predictor of MACEs and mortality in hospitalized patients. Trial Registration: MRCTA, ECFAH of FMU[2024]490